2011
DOI: 10.1002/hipo.20789
|View full text |Cite
|
Sign up to set email alerts
|

Maturational dynamics of hippocampal place cells in immature rats

Abstract: The ontogeny of neural substrates underlying episodic memory is not well described. Place cells are a surrogate for episodic memory and are important for spatial navigation in rodents. Although place cells are well described in mature brains, the nature of the maturation processes remains uncertain. We now report on the ontogeny of the place cell system in rats between P22 and P43, a time during which there is rapid improvement in spatial behavior. We found that place cells with adult like firing fields were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…However, age-related increases in the number of place cells, spatial coherence and inter-trial stability were noted beyond the end of the third postnatal week, along with increases in theta power measured from LFPs and entorhinal grid stability. Many of these developmental changes were corroborated in a later study highlighting an increase in the proportion of adult-like place cells, average spatial signal, and place field stability from P23 to P35 (Scott et al, 2011). No studies have yet correlated developmental alterations in spatial behavior with place or grid cell metrics or the concomitant increase in theta power (Hasselmo, 2005; Vanderwolf, 1969).…”
Section: First Reports Of the Neural Underpinnings Of Hippocampal mentioning
confidence: 65%
“…However, age-related increases in the number of place cells, spatial coherence and inter-trial stability were noted beyond the end of the third postnatal week, along with increases in theta power measured from LFPs and entorhinal grid stability. Many of these developmental changes were corroborated in a later study highlighting an increase in the proportion of adult-like place cells, average spatial signal, and place field stability from P23 to P35 (Scott et al, 2011). No studies have yet correlated developmental alterations in spatial behavior with place or grid cell metrics or the concomitant increase in theta power (Hasselmo, 2005; Vanderwolf, 1969).…”
Section: First Reports Of the Neural Underpinnings Of Hippocampal mentioning
confidence: 65%
“…Specifically, the developmental onset of contextual fear learning coincides with the onset of training-induced hippocampal immediate early gene expression (Raineki et al 2010), and lesion or inactivation of the hippocampus blocks the formation of context and contextual fear memories in infant rats (Foster and Burman 2010;Raineki et al 2010;Schiffino et al 2011). Therefore, the emerging ability of mice to form context-shock associations at 13-14 d of age may reflect the functional maturation of the hippocampus, which continues to undergo changes in neuron number (Altman and Bayer 1975), dendritic arborization (Rahimi and Claiborne 2007), signaling mechanisms (Paylor et al 1996), synaptic plasticity (Harris and Teyler 1984), and spatial firing (Langston et al 2010;Wills et al 2010;Scott et al 2011) during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that the weights can be learned through a developmental process in which topographically organized representations are initially present to serve as a teacher to the attractor and then disappear (McNaughton et al 2006). The feasibility of these ideas may be tested in experiments that measure the developmental onset of place, grid, and directional signals (Martin & Berthoz 2002, Langston et al 2010, Wills et al 2010, Scott et al 2011). However, there is as yet no consensus theory or model of self-organization of weights of an attractor map, and such a model would help guide interpretation and analysis of the experimental results.…”
Section: Future Directionsmentioning
confidence: 99%